Antifertility Effect of Sirih Leaf (Piper betle L.) Ethanol Extract on Male Wistar Rats Spermatogenesis: Efek Antifertilitas Ekstrak Etanol Daun Sirih (Piper betle L.) Pada Spermatogenesis Tikus Wistar Jantan - Melviana Lubis; Widia Syahfitri (Universitas Tadulako, 2023)
Background: Currently, there are still very limited male contraceptive options. The ideal male contraceptive is still needed and ideally has the characteristics of having sufficient effectiveness, fully reversible and safe for long-term use. Several studies have been conducted to explore Piper betle as a contraceptive. Objectives: This study aims to examine the effect of 96% ethanol extract of sirih leaf (Piper betle L.) in reducing rat spermatogenesis quality, which includes the number, concentration, motility and morphology of male rat sperm. Material and Methods: This study used a posttest design with 28 white male rats. The rats were divided into four groups, each consisting of 7 rats. Group I was a control group. The test groups were group II, III, IV, and V, and each received an ethanolic extract of Piper betle leaves with various dosages of 200, 400, and 800 mg/kg body weight (BW), respectively, for 30 days. On day 31, all mice were sacrificed and analyzed for sperm count and concentration, sperm motility and sperm morphology. Results: The administration of 96% Piper betle leaves ethanol extract (PBEE) decreased the number and concentration of rats sperm, decreased progressive sperm motility and reduced the proportion of normal morphological rat sperm. PBEE at 800 mg/kg BW dose showed the greatest decreasing effect among all doses (p = 0.01). Conclusions: PBEE has contraceptive ability with a mechanism to reduce sperm count and concentration, sperm motility and sperm morphology.